Strategies for Understanding Price Perception to Drive Purchasing Decisions - Ali Amzah; Mhd. Habbil Frizky; Dea Ananda Pratama Hutabarat; Rahmi Syahriza (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
Price perception is a crucial factor in consumer decision-making, especially in competitive markets such as coffee shops. This study investigates how price perception influences purchase decisions at Coffee Shop Dubo, utilizing Deep Interviews and Coaching methods. Findings indicate that the shop's previous pricing strategy was perceived as high due to misalignment with consumer expectations. Post-training, the shop implemented more suitable pricing strategies, which improved consumer perceptions of affordability and positively impacted sales. The research underscores the importance of aligning pricing with perceived value and service quality. Effective pricing strategies, combined with high-quality customer service, can enhance price perception and drive customer loyalty. In a competitive coffee shop market, balancing consumer expectations with appropriate pricing is essential for maintaining a strong market position and ensuring long-term business success.